CONDITIONALLY PATHOGENIC MICROFLORA IN PATIENTS WITH BACTERIAL VAGINOSIS - Баринов, Сергей Владимирович; Охлопков, Виталий Александрович; Бабаева, Туран Шахин кызы; Синельникова, Людмила Борисовна; Терлецкая, Татьяна Викторовна (Mother and Baby in Kuzbass, 2019)
The aim of the research. To study the composition of vaginal microflora in patients with bacterial vaginosis (BV), to determine the role of conditionally pathogenic microorganisms in the development of recurrence of this disease. Materials and methods. The investigation covered 50 female patients with a clinical diagnosis of bacterial vaginosis. All patients were randomized into 2 groups: group 1 (25 patients) who received systemic nitroimidazole therapy, group 2 (25 patients) who received systemic nitroimidazole and clindamycin locally. For the diagnosis of BV, Amsel criteria are used. All patients were tested for real-time polymerase chain reaction (Inbioflor) and microbiological studies on the determination of the sensitivity of microorganisms to antibiotics. Control tests were carried out a month after treatment. Results. DNA of Gardnerella vaginalis was detected in all women. Prevotella and Atopobium vaginae were most often detected. A microbiological examination revealed 15 species of conditionally pathogenic microorganisms, most commonly G. vaginalis and Escherichia coli were detected. A recurrence of the disease was detected in 20 % of cases (10 patients). In women with recurrence during the initial examination more than one microorganism was found, most often it was Prevotella, Atopobium, Streptococcus. In 9 patients more than one microorganism remains in the vagina after treatment. Conclusion. In bacterial vaginosis there is a large species diversity of microflora. Requires additional antibiotic therapy aimed at concomitant microflora, which is not affected by standard drugs for the treatment of bacterial vaginosis.